2010
DOI: 10.1002/adsc.200900767
|View full text |Cite
|
Sign up to set email alerts
|

Resorcin[4]arene‐Derived Mono‐ and Diphosphines in Suzuki Cross‐Coupling

Abstract: Three resorcin [4]arene cavitands (1-3) having either one or two resorcinolic C-2 atoms substituted by a À CH 2 PPh 2 podand arm were assessed in the Suzuki arylation of aryl bromides with phenylboronic acid. Using P:Pd ratios of 2:1 and operating in dioxane at 100 8C with a catalyst loading of 0.001 mol% resulted in highly efficient catalytic systems. For example, TOFs up to 34570 mol(converted ArBr)·mol(Pd) À1 ·h À1 were obtained with the proximally-disubstituted cavitand 3 when using 4-bromotoluene as subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…The catalytic efficiency of cavitand‐based phosphines is not necessarily related to the receptor or confining properties of the cavity. Thus, it was found that cavitand phosphine 3 having its P atom separated from the cavity by a methylene group resulted, in the presence of Pd II , in a fast Suzuki–Miyaura (SM) cross‐coupling catalyst The reaction rates were found to be 5–7 times faster than that those observed with PPh 3 . A possible explanation is that during the catalytic process intermediates are formed in which one of the O atoms close to the P forms with this atom a chelate ring.…”
Section: Catalytic Chemistry With Cavitands Substituted With P Donorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The catalytic efficiency of cavitand‐based phosphines is not necessarily related to the receptor or confining properties of the cavity. Thus, it was found that cavitand phosphine 3 having its P atom separated from the cavity by a methylene group resulted, in the presence of Pd II , in a fast Suzuki–Miyaura (SM) cross‐coupling catalyst The reaction rates were found to be 5–7 times faster than that those observed with PPh 3 . A possible explanation is that during the catalytic process intermediates are formed in which one of the O atoms close to the P forms with this atom a chelate ring.…”
Section: Catalytic Chemistry With Cavitands Substituted With P Donorsmentioning
confidence: 99%
“…Their higher performance was attributed to the formation of complexes with PMP angles larger than 90℃, these resulting either from steric repulsions occurring in cyclic oligomeric intermediates (which may form with ligand 5 ) or arising from the formation of strained chelate complexes (which may form with ligand 6 ). Larger PMP angles are known to favor the final reductive elimination step of the catalytic process …”
Section: Catalytic Chemistry With Cavitands Substituted With P Donorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bulky phosphines are known to be some of the most influential ligands for this reaction. Among various bulky phosphines, biphenyl phosphines, phosphapalladacycles, phosphabarrelenes, hemilabile phosphines, indolyl phosphine, ferrocenyl phosphines, resorcinarenyl phosphines, etc., have proven to be of great value in activating difficult substrates including less reactive aryl chlorides. For many years, the ligand bis[2‐(diphenylphosphino)phenyl]ether (DPEphos) has been used as a sterically hindered wide‐bite‐angle diphosphine that has attracted tremendous attention in catalysis because of its commercial availability and interesting chemistry .…”
Section: Introductionmentioning
confidence: 99%
“…We have recently started a programme aimed at the use of resorcin [4]arene-derived cavitands as platforms for the preparation of expanded ligands. [28][29][30][31] Among these, the imidazolium salts 1-3, which are precursors of N-heterocyclic carbene (NHC) ligands, efficiently promote palladiumcatalysed cross-coupling between arylboronic acids and aryl halides. [32] This remarkable efficiency was attributed to a combination of steric bulk provided by the resorcinarenyl fragment and to the presence of oxygen atoms within the macrocyclic backbone that are able to temporarily coordinate the metal centre.…”
Section: Introductionmentioning
confidence: 99%